PENCITRAAN PASANGAN JOKO WIDODO – BASUKI TJAHAJA PURNAMA DALAM IKLAN KAMPANYE VERSI “JAKARTA BARU” (Studi Analisis Semiotik Iklan Televisi) - Irmania Yunita; Ainur Rochmaniah; Nur Maghfirah Aesthetika (Kanal: Jurnal Ilmu Komunikasi, 2013)
The objective of this study is to analyze the meaning contained in communication symbols in the version of "New Jakarta" campaign advertisement of Joko Widodo - Tjahaja Basuki Purnama in television, how the messages conveyed through the advertisement sets the image of Joko Widodo - Tjahaja Basuki Purnama at Jakarta election 2012, and the perception of some viewers from the author point of view. This type of study is a qualitative descriptive using communication semiology analysis approach. As a descriptive study, it only describes the situation or discourse, does not look for a relationship, tests hypotheses or makes predictions. This study uses qualitative data so the data are substantive categories which are then interpreted by scientific references. In the data analysis, the author uses Roland Barthes' semiotic system with the concept of denotation and connotation as the first level, mythologies (myth) as the second level, as well as metonymy and metaphor as the concept of intertextual. The result of study show that the image of Joko Widodo - Tjahaja Basuki Purnama is found in the couple’s self-claim that they are agents of change who can bring people's expectations about the city of Jakarta into real, namely for a better condition of the road in the city, regular city planning, cleanness and flood prevention.